High Linearity Push-Pull Amplifier-Scaler Current on Bipolar Transistors with the Grounded Load - Azarov, O. D.; Heneralnytskyi, Ye. S. (Visnyk of Vinnytsia Politechnical Institute, 2019)
Traditionally, the vast majority of electrical amplifying devices are based on voltage or current amplifiers with voltage output. They are used as elements in the ADC and DAC, as well as in information-measuring and recorded systems, signal generators in direct digital synthesis systems. This is due to the well-established theory and practice of designing such amplifiers. At the same time, in some cases it is more expedient to have operational amplifiers with current output, which can work with a grounded load. Mentioned modern devices and systems are built using integrated circuits. It should be born in mind that most of the parasitic parameters of these circuits are capacitances, and the voltage according to the second switching law cannot jump abruptly on the capacitance, then the speed of the amplifying devices can be greater if all operations on the signals are performed using current amplifiers rather than voltage amplifiers. Therefore, to maximize the use of the frequency properties of bipolar transistors, it should be used as a current amplifier. A controlled current generator can be quite easily obtained on the basis of an operational amplifier by including loads in the feedback circuit, but in this case it cannot be grounded, which narrows its capabilities. It is proposed that controlled current generators with a grounded load are to be constructed on the basis of a push-pull amplifier and current mirrors included in the negative feedback circle on bipolar transistors. However, this approach is new, almost not considered in the scientific and technical literature, therefore the topic of the article devoted to the creation of highly linear push-pull amplifiers — current scalers on bipolar transistors with a grounded load is relevant. A new method for constructing controlled current-to-current generators implemented on bipolar transistors is analyzed, in which negative feedback is based on the removal of current using current mirrors. Mathematical expressions are obtained that make it possible to set the values of current amplification factors and determine the output resistance of a DC amplifier. Computer simulation of the characteristics of a DC amplifier was carried out, the results of which confirm the possibility of their use in high-precision electronic circuits, in particular in multi-bit (n = 16…20) ADCs and DACs.